Tourism Development And Revitalization Of Malaysian Small Towns: Case Study Of Lumut, Perak - Chye, Onn Teck (2018)
This study is an attempt to identify a list of tourism development strategies that can be effective in revitalizing small Malaysian towns. It seeks to address the problem of urban decline. As the nation moves towards achieving developed nation status in 2020, many of the country’s older towns are in a state of decline, involving social, economic and environmental issues. Urban decline is a serious problem as it is related to the health, lifestyle and livelihood of the citizens. Addressing this problem is, therefore, an important and urgent matter. This study proposed that the revitalization of declining towns should be accomplished by the application of tourism development strategies.